The Harvard Semitic Museum Palmyrene Collection - Cussini, Eleonora (Bulletin of ASOR, 2018)
Three Palmyrene funerary busts are part of the collections of the Harvard Semitic Museum. This article discusses the epitaphs, the portraits, and their stylistic features, summarizes the funerary busts' documented history of possession, and offers a palaeographic analysis of the inscriptions.